Alternatipathes longispina sp. nov. and Bathypathes longicaulis sp. nov., two black corals (Antipatharia, Schizopathidae) from seamounts in the Western Pacific - Lü, Ting; Zhan, Zifeng; Li, Yang; Xu, Kuidong (Zootaxa, 2024)
Members of the order Antipatharia Milne-Edwards & Haime, 1857 are important structural components of hard bottom communities in the shallow and deep seas. However, their diversity in the Western Pacific is poorly known. Here we describe two new species of black corals within the family Schizopathidae Brook, 1889 from the tropical Western Pacific seamounts: Alternatipathes longispina sp. nov. and Bathypathes longicaulis sp. nov. The new species Alternatipathes longispina is characterized by a monopodial and unbranched corallum with the maximum width nearly two times as long as the height, the lower unpinnulated section of stem slightly shorter than the upper pinnulated one, the pinnules decreasing in length from the lowermost ones to the uppermost, and the prominent polypar spines ranging from 0.29 mm to 0.58 mm high, such a feature make the species differ from all congeners. Bathypathes longicaulis sp. nov. is characterized by a monopodial and unbranched corallum with a much longer unpinnulated stem and alternately arranged pinnules along the upper part of stem. It can be distinguished from congeners by its much longer unpinnulated stem, the alternately arranged pinnules, and the number of pinnules. Phylogenetic analyses based on the nuclear internal transcribed spacer region (ITS1-5.8S-ITS2) and three mitochondrial fragments cox3-IGR-cox1, trnW-IGR-nad2 and nad5-IGR-nad1 shows that A. longispina sp. nov. clusters with the type species A. bipinnata, and the genus Alternatipathes is closely related to Umbellapathes. The present phylogenetic trees confirm the polyphyly of Bathypathes and show that B. longicaulis sp. nov. is sister to Telopathes cf. magna MacIsaac & Best, 2013.